Corrosion evolution of 2205 duplex stainless steel in hot concentrated seawater under intermittent vacuum and boiling conditions. (December 2021) - Yang, Yong; Liu, Lele; Bi, Hongyun; Zeng, Hongtao; Hou, Xueling; Li, Moucheng
Abstract: Long-term corrosion behavior of 2205 duplex stainless steel was investigated in the hot concentrated artificial seawater under intermittent vacuum boiling and atmosphere conditions during the immersion of more than one year by using electrochemical impedance spectroscopy (EIS). Compared to the atmosphere state, the passive film formed on specimen surface is thinner and the induction time for pitting corrosion decreases notably under intermittent vacuum boiling condition. However, the pit propagation is retarded by the lower dissolved oxygen content and violent boiling of solution. The vacuum boiling of solution has opposite effect on the initiation and stable growth processes of pitting corrosion. Highlights: The vacuum boiling reduces the corrosion resistance and pitting induction time. The lower oxygen content at vacuum boiling state limits the cathodic reaction process. The vacuum boiling has opposite effect on the pit initiation and growth processes.